Parent-Adolescent Discrepancies Regarding Adolescents’ Peer-Related Loneliness: Associations with Adolescent Adjustment - Spithoven, Annette W. M.; Vanhalst, Janne; Lodder, Gerine; Bijttebier, Patricia; Goossens, Luc (Journal of youth and adolescence, 2017)
Because loneliness is a subjective experience, it is often examined using self-reports. Yet, researchers have started to use other-reports to examine loneliness. As previous research suggests that discrepancies between self- and other views might have important implications for adolescents’ mental health, the current study examines discrepancies in multi-informant reports on adolescents’ loneliness in relation with prosocial behavior, aggression, and adolescents’ parent-related loneliness. The sample consisted of 374 mother-adolescent dyads and 318 father-adolescent dyads (41.80% male, M age = 15.67 years, SD = 1.25). Results indicated that informants used different reference points to assess adolescents’ peer-related loneliness, but were otherwise comparable. Moreover, informant discrepancies were associated with greater adolescents’ reported parent-related loneliness. The current study did not provide evidence that discrepancies were related to prosocial or aggressive behavior. The current study adds to the notion that other-reports on loneliness show substantial convergence with self-reports. In addition, this study indicates that the discrepancy between other- and self-reports on loneliness holds valuable information for adolescent socio-emotional adjustment.